Designing the Future of Education:: An Integrative Strategic Planning Model Based on Internal and External School Environment Analysis - Hamam Nasrudin; Nur Khamilah; Aizza'ul Widad; Ari Riwayanto; Ngurah Ayu Nyoman (Nur Science Institute, 2026)
Background: This study aims to develop an integrative strategic planning model based on internal and external environmental analysis. Method: A systematic literature review (SLR) was employed to synthesize findings from ten selected articles published in SINTA 1 and SINTA 2 indexed journals within the last five years. The analysis followed the PRISMA framework and utilized SWOT and TOWS approaches to identify and formulate strategic factors. Result: The findings reveal that educational institutions possess key strengths such as innovative pedagogy, student learning autonomy, collaborative supervision, and active stakeholder involvement. However, several weaknesses were also identified, including academic procrastination, disparities in teacher capacity, and limited resources. From an external perspective, opportunities arise from global initiatives such as the Sustainable Development Goals (SDGs), increasing digital literacy awareness, and supportive educational policies, while threats include bullying, rapid technological disruption, and increasing institutional competition. Based on these findings, four strategic orientations were formulated (SO, ST, WO, WT), which were then synthesized into an integrative strategic planning model. The proposed model emphasizes the integration of three strategic domains: operational, managerial, and empowerment strategies. Novelty: This study contributes theoretically by offering a holistic framework for educational strategic management and practically by providing a structured guideline for developing adaptive and sustainable educational strategies.